Wikipedia: quotations at the interface of encyclopedic and participatory practices - Kleinke, Sonja (Journal of pragmatics, 2020)
Due to its genuinely participatory practices, quotations in Wikipedia entries are dynamically and collectively negotiated and revised by members of the broader public against the background of Wikipedia's central editing principles. Hence, quotations are an essential elaboration site of competing encyclopedic and participatory practices. This paper aims to show how Wikipedia authors, in modifying the context, focus and perspective of source material, engage in complex processes of framing and reframing of the source material and their participatory activities. These framing activities not only concern the quote-worthiness of source material and users' academic and/or participatory aspirations, but are also carried out at an interpersonal level and thus contribute to new dimensions of public encyclopedia-writing and reflective participatory discourse “from below”. To scrutinize these processes, this paper examines the types and functions of quotations in two highly contested example articles (Nation and Brexit) and their respective Talk-sections as retrieved in September 2017 (Nation) and December 2017 (Brexit), with a total of 49500 words. Corresponding to the two different discourse environments, contributors to both articles use quotations primarily in their indexical and argumentative functions. By contrast, quotations in the Talk-section mainly serve interpersonal and metapragmatic functions, sometimes intertwined with argumentative functions.
Available online 19 September 2019
Gesehen am 26.03.2020